Intramolecular bonds resolved on a semiconductor surface - Sweetman, Adam; Jarvis, Samuel Paul; Rahe, Philipp; Champness, Neil R.; Kantorovich, Lev; Moriarty, Philip (American Physical Society, 2014)
Noncontact atomic force microscopy (NC-AFM) is now routinely capable of obtaining submolecular resolution, readily resolving the carbon backbone structure of planar organic molecules adsorbed on metal substrates. Here we show that the same resolution may also be obtained for molecules adsorbed on a reactive semiconducting substrate. Surprisingly, this resolution is routinely obtained without the need for deliberate tip functionalization. Intriguingly, we observe two chemically distinct apex types capable of submolecular imaging. We characterize our tip apices by “inverse imaging” of the silicon adatoms of the Si(111)−7×7 surface and support our findings with detailed density functional theory (DFT) calculations. We also show that intramolecular resolution on individual molecules may be readily obtained at 78 K, rather than solely at 5 K as previously demonstrated. Our results suggest a wide range of tips may be capable of producing intramolecular contrast for molecules adsorbed on semiconductor surfaces, leading to a much broader applicability for submolecular imaging protocols.